Influences of technology and data use on the professional self-efficacy of Malaysian teachers - Abdullah, Samsu Hilmy; Mohd Puad, Mohd Hazwan; Azmi Murad, Masrah Azrifah; Marlisah, Erzam (South East Asia Association for Institutional Research, 2024)
The trend of early retirement among teachers is worrisome as it results in the loss of experienced teachers and contributes to the expanding teacher shortage. This condition is thought to have been caused by the workload and strain connected with technology and data use. Early retirement signifies teachers’ burnout, stress, and lack of job satisfaction, and multiple studies have suggested that they significantly affect professional self-efficacy. This article explores the influence of technology and data use on a teacher's self-efficacy in relation to their profession. A total of 525 school teachers in Malaysia have participated in a research study by completing a questionnaire. The results indicated that teacher professional self-efficacy, technology use, and data use are at a moderate level. The findings demonstrate a favorable correlation among these constructs. However, the connections are not influenced by factors such as age, gender, or school location. The study's implications for the higher education setting are also addressed, suggesting the implementation of enhancement of professional development opportunities, mentorship and peer support, and recognition to teachers. These suggestions aim to better equip teachers with the indispensable skills required in the swiftly evolving realm of data and technology.